The Lithuanian political party image assessment questionnaire: Adaptation by modification - Gorbaniuk, Oleg; Ivanova, Ana; Blėkaitytė, Dovilė; Budraitytė, Gintalija; Pakalnytė, Emilija Salomėja (Psichologija, 2017)
As today’s political market change leads to the personification of politics, research conducted in various countries supports the idea that ideological differences have less influence on the electoral decisions than in the past (Caprara & Zimbardo, 2004; King, 2002; McGraw, 2008; Wattenberg, 1991). On the other hand, the significance of personal characteristics is increasing, since perceived political leaders’ personality traits are transmitted by voters to the parties through the process of personification (Hayes, 2005). Scientists in today’s source literature haven’t developed a uniform instrument for political party image assessment that considers the specificity of the subject, whereas a new proposition of such an instrument has been evolved on the base of lexical research (Gorbaniuk, Kusak, Kogut, & Kustos, 2015).The aim of the current study was to adapt the Political Party Image Assessment Questionnaire into the Lithuanian language and to evaluate its psychometric properties. Moreover, this study was conducted to answer the question if political preferences have explanatory power. Quantitative research was conducted on the sample of 300 Lithuanian students (50.5% female), who had to describe 6 well-known political parties using 25 adjectives. A confirmatory factor analysis was arranged with the complete data set. Because only the five-factor model was acceptable, the entire sample was randomly split into approximate 50% halves. The exploratory factor analysis was arranged with the training group data set, and the confirmatory factor analysis was used in the validation set. Both analyses showed that the six-factor solution ((1) strength, (2) integrity, (3) disagreeableness, (4) religious conservatism, (5) left-wing vs. right-wing, (6) backwardness vs. modernity) was regarded as an optimal model to explain the specificity of Lithuanian political party perception. Also, the measurement invariance of this instrument was tested across 6 parties. Configural, metric and factor covariance invariance were established for all parties. Explanatory power of political party image dimensions was confirmed by a multiple regression analysis. Moreover, the test-retest with 14–20 days interval between the first and the second measurements showed a satisfying stability of scores.The current study was conducted to present the Lithuanian version of the Political Party Image Assessment Questionnaire, whose psychometric properties resulted in satisfying values.
Keywords: image; political party; attitude; political preferences